Recalled maternal rearing behaviour of individuals born preterm and their mothers: the impact of intimate mother-child contact - Otten, Daniëlle; Ernst, Mareike; Schuster, Alexander K.; Tesarz, Jonas; Gißler, Sandra; Mildenberger, Eva; Pfeiffer, Norbert; Beutel, Manfred; Fieß, Achim (Journal of Clinical Medicine, 2024)
Background: Preterm birth is a risk factor for a variety of detrimental health outcomes. Previous studies have identified recalled (or remembered) parental rearing behaviour as a potential modifier of preterm individuals’ mental health in adulthood. However, no investigations to date have contrasted the parents’ and children’s views, explored whether their congruence is associated with preterm individuals’ mental health, or tested associations with maternal self-reported first skin-on-skin contact. Methods: This cohort study involved 199 participants of the Gutenberg Prematurity Eye Study (GPES), with prospective clinical examination and psychological assessment data available for individuals born preterm and term and their mothers’ perspective on recalled parental rearing behaviour. Participants also completed the Patient Health Questionnaire-9 (PHQ-9). Results: There were substantial similarities between reported recalled maternal rearing behaviour of individuals born preterm and at term and their mothers, with individuals born preterm with lower gestational age (age of the pregnancy from the woman’s last menstrual period) recalling mothers as comparatively more controlling and overprotective. Incongruence in recalled rejection/punishment was associated with more depressive symptoms. Late first skin-to-skin contact was related to more recalled maternal rejection/punishment, less emotional warmth, and more control/overprotection. Conclusions: this study expands the knowledge about the interrelations of preterm birth, maternal rearing behaviour, and mental health, underscoring the relevance of first relationship experiences, including close intimate contact.